PERAN UNI EROPA DALAM MEMBANTU MENGATASI KRISIS UTANG DI YUNANI TAHUN 2010-2014 - Muhammad Fadhli Ardiansyah (HI 16 UMY 082, 2016)
*82 This article shown how European Union help Greece to overcome its debt crisis. To answers â€œhows EU role to help Greece to overcome its debt crisis. To respond those question this writing using â€œpublic policyâ€ consept. This consept used to see how EU as the International Organization control Greece as a country because at that time Greece political condition is a mess because of disclosure about its government spending, so EU give Greece bailout to prevent Greece default. Key Word: Public Policy, Economic Crisis, European Union, Bailout, Reformasi Ekonomi, Austerity